Transfer of learning from traditional optics to wavefront aberrometry - McBride, Dyan L. (Kansas State University, 2009)
This research presents an investigation of how students dynamically construct knowledge in a new situation. In particular, this work focuses on the contexts of light and optics, and examines the dynamic construction of an understanding of wavefront aberrometry. The study began with clinical interviews designed to elicit students’ prior knowledge about light, basic optics, and vision; the data were analyzed phenomenographically to obtain student models of understanding and examine the possible model variations. The results indicate that students have a significant number of resources in this subject area, though some are incomplete or less useful than others. In subsequent phases, many learning and teaching interviews were conducted to design and test scaffolding procedures that could be of use to students as they constructed their understanding of the given phenomenon. Throughout this work, student responses were analyzed in terms of the resources that were being used through the knowledge construction process. Finally, a modified analysis method is presented and utilized for quantifying what types of concepts students use while constructing their understanding, and how they are able to link varying types of concepts together. Significant implications extend beyond the single context of wavefront aberrometry. Each distinct analysis technique provides further insight to the ways in which students learn across contexts and the ways in which we can scaffold their learning to improve curriculum and instruction.
Keywords: Transfer of learning; optics; wavefront aberrometery; Physics, General (0605)